O cultivo de tilápia do Nilo Oreochromis niloticus em tanques-rede em reservatório do semiárido brasileiro é sustentável economicamente, socialmente e ambientalmente? - Cacho, Júlio César da Silva (Universidade Federal Rural do Semi-Árido, 2017)
Concerns regarding the sustainability of aquaculture enterprises as well as the modifications that they can provide to aquatic environments are fundamental in water bodies, mainly in semi-arid reservoirs, where occurs a constant water scarcity. Thus, this work aimed to evaluate the sedimentation of nutrients and particulate matter, as well as the environmental, social and economic sustainability of a tilapia breeding system in net cages in a Brazilian semi-arid reservoir. The study was conducted in a cooperative of entrepreneurs who manage a Nile tilapia production in net cages in the reservoir Umari (5°42’13”S and 37°15’18”O). The sediment generated by the net cages was analyzed, as well as were used 40 sustainability indicators, being the system sustainability modeled through the theoretical Drivers-Pressure-State-Impact-Response framework, in which two scenarios were considered. real breedings, which operated with stocking densities of 100 and 125 fish/cage, with four cycles of annual breeding (DENS 100 CC; DENS 125 CC, respectively) and two hypothetical scenarios considering a density of 100 and 125 fish/cage, with two annual breeding cycles (DENS 100 CL, DENS 125 CL, respectively). The sedimentation rates in the net cages were significantly higher when compared to the observed rates in the reservoir region without the influence of the net cages, demonstrating that the fish farming activity in net cages raises the sedimentation rates of nutrients and particulate matter in this reservoir, what may contribute to accelerate the eutrophication process of this aquatic environment. However, the results showed that the sedimentation rates increase was punctual, that is, still is restricted to the fish farming in net cages region in the Umari reservoir. From the comparison between the scenarios provided by the modeling, it was evident that the real breedings despite have presented better performance in environmental and social sustainabilities were not viable from the economic point of view, which may cause the end of the enterprise and consequently the reduction of social benefits for the local population. The modeling also demonstrated that alterations in the increase of the breeding time and the consequent decrease of the annual production cycles, increased the sustainability in a global way, but at the same time reduced the environmental sustainability, being important to highlight that as a result of the semiarid region presents peculiar characteristics with relation to the water scarcity, the low environmental sustainability of the intensive fish farming activities in net cages carried out in these reservoirs may in the medium term economically and socially compromise the activity
Is nile tilapia (Oreochromis niloticus) breeding in net cages in brazilian semi-arid reservoir economically, socially and environmentally sustainable?
Keywords: Taxas de sedimentação; Indicadores de sustentabilidade; Modelagem; Sistema de cultivo; Sedimentation rates; Sustainability indicators; Modeling; Cultivation system; CIENCIAS AGRARIAS::MEDICINA VETERINARIA